Self-directed learning is fine - if you know the destination! - Briguglio, Carmela (Curtin University of Technology, 2000)
Many international students in Australian tertiary institutions are studying in what may be their second or third language. While the current status of English as a 'world language' makes it highly desirable to have a degree in that language, undertaking tertiary study in a second/ foreign language is no easy matter, nor should some of the difficulties be underestimated.This paper supports the view that the aim of tertiary study is to develop learners who are independent, confident and self directed. However, it raises the issue that international students, at least in the initial stages of their sojourn in Australia, may require a more structured approach than self directed learning would seem to imply. The paper then describes some of the strategies that support international students in making the transition to study in an Australian tertiary institution and suggests further steps that will, gradually, lead such students to become confident and independent learners who will develop their full potential.